PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KOMPETENSI DASAR KEILMUAN MAHASISWA PADA PERKULIAHAN FISIKA TERAPAN - Zainuddin Zainuddin (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2011)
Abtract: The general purpose of this action research is to describe the effectiveness of Problem Based Learning Model in improving the student’s scientific basic competence in Applied Physic Lecture. To study the application of physics in technology and physics problems solving in this course, is needed the scientific basic competencies as skills to analyze components of equipment, explain the working principles of physics technology products, and describe how the application of physics to overcome the life issues. This research showed that the Problem Based Learning Model was effective to improve the student’s scientific basic competencies by 74.8% effectivity score.Key words: scientific basic competence, applied physics. problem based learning